Based on the immune system: the role of the IL-2 family in pancreatic disease - Zhu, Yuqing; Lu, Zheng; Wang, Zhuo; Liu, Jiao; Ning, Ke (Frontiers in Immunology, 2025)
The IL-2 family, consisting of IL-2, IL-4, IL-7, IL-9, IL-15 and IL-21, is a key regulator of the immune response. As an important endocrine and digestive organ, the function of the pancreas is regulated by the immune system. Studies have shown that each cytokine of the IL-2 family influences the occurrence and development of pancreatic diseases by participating in the regulation of the immune system. In this paper, we review the structural and functional characteristics of IL-2 family members, focus on their molecular mechanisms in pancreatic diseases including acute pancreatitis, chronic pancreatitis and pancreatic cancer, and highlight the importance of the related proteins in the regulation of immune response and disease progression, which will provide valuable insights for new biomarkers in pancreatic diseases, early diagnosis of the diseases, assessment of the disease severity, and development of new therapeutic regimens. The insights of the study are summarized in the following sections.